2003
DOI: 10.1016/s0029-7844(02)02712-6
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin's effects on hot flashes in postmenopausal women: a randomized controlled trial

Abstract: Gabapentin is effective in reducing hot flash frequency and severity in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(164 citation statements)
references
References 36 publications
6
157
0
1
Order By: Relevance
“…37 In 2 placebocontrolled, double-blind, randomized clinical trials, investigators demonstrated that gabapentin does reduce hot flashes in women with and without a history of breast cancer. 13,14 Mean hot flash score reduction in 1 of these studies 13 with 59 postmenopausal women was 54% compared with a 31% reduction with placebo. In the other trial, 14 involving 360 women, a 30% reduction in hot flash scores after 8 weeks was reported for patients receiving gabapentin 100 mg 3 times daily compared with a 46% reduction for 300 mg 3 times daily and an 18% reduction with placebo.…”
Section: Gabapentinmentioning
confidence: 94%
See 3 more Smart Citations
“…37 In 2 placebocontrolled, double-blind, randomized clinical trials, investigators demonstrated that gabapentin does reduce hot flashes in women with and without a history of breast cancer. 13,14 Mean hot flash score reduction in 1 of these studies 13 with 59 postmenopausal women was 54% compared with a 31% reduction with placebo. In the other trial, 14 involving 360 women, a 30% reduction in hot flash scores after 8 weeks was reported for patients receiving gabapentin 100 mg 3 times daily compared with a 46% reduction for 300 mg 3 times daily and an 18% reduction with placebo.…”
Section: Gabapentinmentioning
confidence: 94%
“…Eligibility criteria were not specified. The outcome measure was an interview at the end of each 13 RPCT , 12 wk 59 MW 54 31 Light-headed, dizzy, mild peripheral edema, decreased serum albumin Gabapentin 14 RPCT, 8 wk 360 BC -100 mg tid 30 18 300 mg tid 46 18 BC ϭ women with a history of breast cancer; CR ϭ controlled release; ER ϭ extended release; MW ϭ menopausal women; RPCT ϭ randomized placebo-controlled trial.…”
Section: Bellergalmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Gabapentin may be beneficial for the symptoms of aches, pains and paraesthesia that many menopausal women experience. Interaction may occur with antacids and side-effects include dizziness, fatigue, tremor, ataxia, arthralgia and weight increase.…”
Section: Gabapentinmentioning
confidence: 99%